Application of 6 MeV LINAC in Food Industries: Enhancement of shelf life of onion, Potato and Mango. (June 2022) - Asif, Anum; Qureshi, Tariq M.; Zeeshan, Sumaira; Sher, Falak; Ayub, M.; Yaqub, Kashif; Baig, AnisUllah; Rehman, Abdul; Asif Khan, M.
Abstract: Electron LINACs are extensively used for medical and industrial applications worldwide. Pakistan has been using LINACs in the medical field for many years and is now working on indigenous development of electron LINAC considering its great demand and multiple applications. A major portion of Pakistan's economy is dependent on export of agricultural products, which get wasted due to improper management and deficiency of resources to extend the shelf life of products resulting in lack of compliance with international market requirements. Food irradiation is an effective method to enhance the shelf life of agricultural products to boost country's export. For this purpose, indigenously developed low dose 6 MeV LINAC has been used to test its suitability and applicability in the food irradiation field. Experiments have been performed on onions and potatoes to inhibit sprouting and on mangoes to increase their shelf life by delaying rotting on exposing them with low dose X-rays LINAC. Results of first experiment indicated inhibition of sprouting to more than 24 weeks post irradiation. The validity and acceptability of irradiation technology requires no effect of irradiation on nutritional contents of samples. For this purpose treated and controlled potato and onion samples are tested for nutritional contents, which showed successful results and no marked effects were observed on contents like moisture, ash or protein. Prolongation of life of fully ripened mangoes with low dose of X-rays is found successful enough to increase shelf life to more than double as compare to non-irradiated (controlled) mangoes. Highlights: 06 MeV LINAC used for food irradiation studies. Sprout inhibition observed in irradiated onions and potatoes. The X-rays dose has minimal effect on nutrition value of the food items. Bigger size vegetables are preferable for irradiation with minimal effect on nutrition. X-ray irradiation has doubled the shelf life of fully ripened mangoes.